Field evaluation of the CRT and ACON chlamydia point-of-care tests in a tropical, low-resource setting. (13th December 2013) - Hurly, D S; Buhrer-Skinner, M; Badman, S G; Bulu, S; Tabrizi, S N; Tarivonda, L; Muller, R
Abstract : Objective: To evaluate the clinical performance of two chlamydia point-of-care (POC) tests compared with a gold standard nucleic acid amplification testing (NAAT). Methods: Tests evaluated were the Chlamydia Rapid Test (CRT), Diagnostics for the Real World and the ACON Chlamydia Rapid Test Device, ACON Laboratories (ACON). Overall 226 men and 225 women in Port Vila, Vanuatu, participated in this prospective study in 2010. NAAT and POC testing was performed on samples of male urine and female vaginal swabs for 156 men and 223 women (CRT), and 133 men and 75 women (ACON). Results: The sensitivity and specificity of the CRT in men were 41.4% (95% CI 23.5% to 61.1%) and 89.0% (95% CI 82.2% to 93.8%), respectively, and in women 74.2% (95% CI 61.5% to 84.5%) and 95.7% (95% CI 91.3% to 98.2%), respectively; for ACON, they were 43.8% (95% CI 19.8% to 70.1%) and 98.3% (95% CI 93.9% to 99.8%) in men, and in women 66.7% (95% CI 22.3% to 95.7%) and 91.3% (95% CI 82.0% to 96.7%), respectively. Both tests were (absolutely) insensitive at organism loads less than 1000 (log=3) per mL or per swab; the CRT sensitivity was significantly lower at loads less than, compared with those greater than, 100 000 (log=5) per mL or per swab. Conclusions: The performance of both CRT and ACON is well below the levels stated by the manufacturers. The evaluated tests are unlikely to be helpful in clinical settings due to the high proportion of false-negatives that will go untreated and false-positives that will result in overtreatment and potential adverse social consequences.